Fiscal Multipliers in the ECCU - Gonzalez-Garcia, Jesus (IMF Working Papers; Working Paper ;, 2013)
The multipliers of taxes, and government consumption and investment expenditure for the Eastern Caribbean Currency Union (ECCU) are estimated using vector autoregression models with panel data. The impact and long-run multipliers are below unity, suggesting that a great extent of the intended impulse ends up expanding imported demand. The long-run multipliers of taxes and consumption expenditure are non-different from zero statistically, while public investment has a long-run multiplier of 0.6. The results suggest that countercyclical policies to stimulate growth should focus on public investment.